Educator Creativity in Transdisciplinary and Crossdisciplinary Approaches to Social Studies Learning at the Junior High School / MTS Level - Hasanah, Nurul; Syaharuddin, Syaharuddin; Triyono, Sigit; Ilhami, M. Ridha; Syarifuddin, Syarifuddin; Jumriani, Jumriani (Universitas Lambung Mangkurat, 2024)
A developed country can be said to prioritize education, arguing that without education a nation will not have the ability to manage to meet the needs of life. The role of an educator has a very important task, role, and position in the world of education. That is why, an educator must always develop his abilities. The method used in writing this article is a descriptive analysis technique with literature study. Collect articles, e-books, journals and other scientific literature obtained from the Google Scholar platform or also called Google Scholar and online e-book books. The creativity of an educator in using learning methods to increase student motivation in junior high school social studies / MTS lessons always tries to increase creativity. In a transdisciplinary or crossdisciplinary view, education must involve the development of human potential and humanity of a student. A learner must develop his personal life which concerns various aspects of personality with regard to social life, culture, religion, art, economy, science and technology as a human being. Education must also develop the human potential of a student such as concern for the environment, society, nation, state, human beings who can make themselves as agents of change in the welfare of community life and use discipline and transdiscipline as tools for the welfare of human life. Teacher Creativity Development in creative learning based on a learning approach is to provide material that is in accordance with life events / experiences. By using a variety of relevant disciplines.